Sticking to minimum standards: implementing antibiotic stewardship in intensive care. Issue 12 (December 2014) - Chaves, N. J.; Ingram, R. J.; MacIsaac, C. M.; Buising, K. L.
Abstract Background In Australia, antimicrobial stewardship programmes are a compulsory component of hospital accreditation. Good documentation around anti‐microbial prescribing aids communication and can improve prescribing practice in environments with multiple decision makers. Aim This study aims to develop and implement an intervention to improve antimicrobial prescribing practice in a 24‐bed intensive care unit in a tertiary referral adult hospital. Methods We conducted a four‐phase (observation, reflection, implementation, evaluation) prospective collaborative before–after quality improvement study. Baseline audits and surveys of antimicrobial prescribing practices identified barriers to and enablers of good prescribing practice. A customised intervention was then implemented over 6 weeks and included a yellow medication record sticker, quarterly education sessions and intensive care unit‐specific empiric antimicrobial prescribing guidelines. Post‐implementation, the effects were monitored by serial antimicrobial prescribing audits for 1 year. The primary outcomes were clear documentation of the start date, the planned stop date or review date and the indication for an antibiotic. These were all considered the 'minimum standards' for an antimicrobial prescription on the medication record. Results Documentation of minimum standards specifically addressed by the sticker improved (start date (72% to 90%, P < 0.001), stop date (16% to 63%, P < 0.001), antimicrobial indication documented on medication chart (58% to 83%, P < 0.01)). Overall, adherence to all three minimum standards (start date, stop date and indication) improved from 41/306 (13%) to 306/492 (63%) (P < 0.001). One‐year post‐implementation, the yellow sticker had become embedded into daily practice. Conclusion A systematic approach to quality improvement combined with the implementation of a tailored, multi‐faceted intervention can improve antimicrobial prescribing practices.